Habitat selection by a despotic passerine, the Bell Miner (Manorina melanophrys): When restoring habitat through Lantana (Lantana camara) removal is not enough. (21st January 2016) - Lambert, Kathryn T. A.; Kumar, Lalit; Reid, Nick; McDonald, Paul G.
Summary: The Bell Miner ( Manorina melanophrys ) occurs in logged eucalypt forest in northern NSW with a dense understorey of the invasive Neotropical shrub Lantana ( Lantana camara ) that is used for nesting. The link between Bell Miners and Lantana is important as the birds aggressively exclude all smaller and similar‐sized birds from their colonies, reducing avian diversity in forest occupied by the species. We monitored the impact of Lantana removal on Bell Miner persistence in several plots in two logged forest sites, along with untreated control plots at one of the sites. Lantana control was successful over 7 years at both sites, with regeneration of native understorey, midstorey and canopy species compensating for the loss of live Lantana cover in the understorey. Bell Miner individuals vacated the treated plots in one site (Creek's Bend) but persisted in the control and treated plots at the second site (Toonumbar National Park). Bell Miner response was correlated with forest structure: birds vacated forest with a sparse understorey (<5 m) but dense midstorey (5–15 m) and canopy (>15 m) at Creek's Bend, but remained at the site with a dense understorey but sparse midstorey and canopy at Toonumbar. We therefore predict that forest restoration that simultaneously reduces Lantana understorey and increases midstorey density will be most successful in reducing the abundance of the despotic Bell Miner and increasing avian diversity in rehabilitated sites.